Effect of Climate Change on Rice Production: A Case of Six VDCs in Jumla District - Sapkota, Sudha; Paudel, Mina Nath; Thakur, Naresh Singh; Nepali, Megh Bahadur; Neupane, Reshma (Nepal Journal of Science and Technology, 2011)
Rice (Oryza sativa L.) is a staple crop of Nepal and is directly associated with ample water and minimum fluctuation of temperature that could affect on its production. Jumla is the unique place where rice is cultivated in the highest altitude (3000 m) in the world. To find out changes in rice production due to climatic effect, six VDCs of Jumla were chosen for the study. Household survey, participatory rapid appraisal, farmers’ group discussions and desk review were used for collecting data. Rice varieties Chandannath-1 andChandannath-3 were disseminated by the formal seed system with the aim of increasing rice productivity. Despite the replacement of local varieties by improved ones the production trend seems to be stagnant. One of the factors on stagnant of rice production in Jumla is due to the lack of desirable variety with genetic traits of early maturity, less nutrient requirement compared to Jumli Marshi to cope up with the climate congruently supporting to cultural practices regarding the unique rice production systems of Jumla. Key words: climate change; rice production; highest altitude; seed DOI: 10.3126/njst.v11i0.4124 Nepal Journal of Science and Technology 11 (2010) 57-62